Bimbingan Rohani Islam dalam Menumbuhkan Motivasi Kesembuhan pada Pasien Jantung - imanda, novia nurul; Muksin, Ucin; Muttaqin, Zaenal (Irsyad: Jurnal Bimbingan, Penyuluhan, Konseling, dan Psikoterapi Islam, 2023)
This study aims to determine the program, process and results of the implementation of Islamic Spiritual Guidance in growing motivation for healing heart patients at Cibabat Hospital. The background of this research is that Islamic Spiritual Guidance in hospitals is a process of providing services to patients to guide patients to gain a sense of sincerity, patience and calm in dealing with the pain they are experiencing. By cultivating healing motivation which is characterized by a positive attitude, goal-oriented, and encouragement. The method used is a descriptive and qualitative approach. The process of Islamic Spiritual Guidance for patients is carried out by visiting the patient to his room and then providing material according to the patient's needs including etiquette and the virtues of dhikr and prayer, worship in illness and the nature of illness and the nature of treatment. The results of this study indicate that Islamic Spiritual Guidance is very important in fostering healing motivation in heart patients.